Solvitur ambulando: The Peripatetic Essay from Leslie Stephen to Virginia Woolf - Marie LANIEL (E-REA)
This paper aims to bring to light some continuities between periodical essays written by Victorian critic Leslie Stephen (1832-1904) and Modernist writer Virginia Woolf (1882-1941), by focusing on a specific type of essay—“the peripatetic essay”—, which uses walking as a structuring device (Forsdick 48) and which both father and daughter quite frequently deployed. Although they were published some fifty years apart, “London Walks” (1880), and “Street Haunting” (1927) testify to their authors’ common interest in the material culture of their times and their rootedness in the English empirical tradition, a tradition epitomized by Stephen’s motto as the leader of the Sunday Tramps: “solvitur ambulando,” “solved by walking” or “solved by practical experience,” which connects empirical proof with perambulation (Maitland 366). The peripatetic essay, because it relies on the “alternation between thought and perception,” “self-consciousness and consciousness of a world beyond the self,” “physical and mental experience” (Gilbert in Forsdick 47-8), allows both writers to firmly root their reflection in bodily sensation. Comparison with Stephen’s essays reveals the magnitude of Woolf’s re-appropriation and revision of the genre: while Stephen’s persona, “a professed misoscopist” or hater of sights (224), refuses to be absorbed or alienated by visual perceptions, using them merely as a “promoter of thought” (234), Woolf’s persona gives precedence to sensation over the intellect, turning into “a central oyster of perceptiveness,” “an enormous eye” (481), as well as an army of conflicting selves, who dissolve the frontiers of personality.